Optimization of a Two-Warehouse EOQ Model for Non-Instantaneous Deteriorating Items with Polynomial Demand, Advance Payment, and Shortages (Contemporary Mathematics, 2024)
In this paper, a two-warehouse inventory model with polynomial time-dependent demand for noninstantaneous deteriorating items is taken into consideration. As advertisement plays a vital role in business, more advertisements are to be made by the retailer to increase demand in the competitive market. In order to meet the high demand, it is necessary to maintain two warehouses to store the goods in inventory: one owned warehouse with limited capacity and one rented warehouse with unlimited capacity. In order to increase sales, the retailer anticipates a discount from the manufacturer, and in turn, the retailer is equipped to pay a portion of the purchase price in advance. The model aims to optimize the overall profit by determining the appropriate order quantity and cycle length. Furthermore, numerical examples are provided for the validation of the proposed model.
Keywords: advance payment; deterioration; intensity of advertisement; capacity constraint